Cost estimation method of IT project based on revised demand get from weighted relational grade - Fang FANG; Zhihua JIN; Yi ZHANG; Hao HAN (Dianxin kexue)
The construction of IT projects in China has entered a stage of rapid development,the problem of the no-clear demand and inaccurate pre-investment estimates in pre-project are exposed.This is the most important reason of IT projects out of control,and it restricts the development of IT projects.The demand of IT project was revised and the relational grade was weighted based on the function point method.The revised demand get from weighted relational grade is beneficial to estimate the costs of the IT projects in pre-project,and it can ensure the orderly completion of IT projects.